PENGARUH STRUKTUR MODAL, PROFITABILITAS, CORPORATE SOCIAL RESPONSIBILITY, DAN FIRM SIZE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2014-2016 - Rafika Hermawati, 14.05.51.0192; Susilowati, Yeye (Students' Journal of Economic and Management, 2018)
This study aims to examine the effect of capital structure, profitability, corporate social responsibility, and firm size on firm value. This research was conducted in Indonesia by using unit of analysis of manufacturing company. The population of this study is a manufacturing company listed on the Indonesia Stock Exchange. Sampling method using purposive sampling with research period 2014 until 2016 and obtained as many as 235 companies. Data analysis technique used is multiple linear regression analysis. The results showed that the capital structure had a significant negative effect on firm value. Profitability has a significant positive effect on company value. Corporate social responsibility negatively affects not significant to company value. Meanwhile, firm size has a significant positive effect on company value.Keyword: Corporate value, capital structure, profitability, corporate social responsibility, and firm size.